From Argentina to the world: Building a network to enhance the capabilities of herbarium collections - Yañez, Agustina (2025)
This article assesses the current state of botanical collections in Argentine herbaria, with a particular focus on data and image digitization, collection management, and the publication of information through publicly accessible repositories. The study employed a survey conducted by the Argentine Herbaria Network (RedHAr) between August 2023 and February 2025 across 44 herbaria to gather detailed insights into the curation and digitization status of their collections. The findings reveal that while many herbaria perceive a good state of physical conservation and have digitized label data, there is a significant limitation in the utilization of specialized software for managing databases in order to automate internal processes such as label generation and recording the movement of specimens (loans, donations, exchanges). Furthermore, there is a consensus on the importance of making specimen information publicly accessible through repositories, although there are still important limitations such as human resources or lack of equipment. Despite efforts to consolidate biological collections and data at the national level, heterogeneity and challenges in the management and dissemination of information are observed. RedHAr aims to develop strategies to incorporate and improve the databases of Argentine herbaria and to democratize access to their collections, recognizing their fundamental value for biodiversity research.